Social work support and unmet social needs in life after stroke: a cross-sectional exploratory study - Sophie Lehnerer; Benjamin Hotter; Inken Padberg; Petra Knispel; Dike Remstedt; Andrea Liebenau; Ulrike Grittner; Ian Wellwood; Andreas Meisel; on behalf of the BSA Long Term Care Study Group (BMC Neurology, 2019)
Abstract Background Stroke patients are often affected by long-term disabilities with needs concerning social issues. There is relatively little consideration of social recovery of patients and the support required to return to work, receive social benefits, participate in daily life activities, maintain contact with family and friends and to organize financial affairs. In our study we aimed to investigate if existing tools record social needs adequately. We analyzed the current provision of social support provided in long-term care after stroke and whether unmet social needs were associated with quality of life, caregiver burden, overall function and degree of disability. Methods Our analysis is part of the Managing Aftercare of Stroke study (MAS-I), a cross-sectional exploratory study of patient needs 2–3 years after initial stroke. Assessment tools included the Nikolaus-score (social situation), the EuroQoL (quality of life), the German Burden Scale for Family Caregivers (caregiver burden), the modified Rankin Scale (disability / dependence), Stroke Impact Scale (function and degree of disability) and the Stroke Survivor Needs Questionnaire (unmet needs). Results Overall 57 patients were included in MAS-I, with ten patients classified in urgent need of socio-economic support according to the Nikolaus-score. Patients with lower than normal Nikolaus-score had a higher degree of disability. Thirty percent of all patients had never received professional social support. Social worker contact happened mostly during the stay in acute hospital or rehabilitation institution. Only four patients (11%) reported long-term support after discharge. Apart from social worker contact during acute care, 43% of patients had unmet needs in the long-term aftercare. Forty percent of all patients included in MAS-I were recommended for social work intervention after an in-depth analysis of their situation. Finally, we saw that unmet social needs were associated with lower quality of life and higher caregiver burden. Conclusions Our data suggest significant unmet needs in social care in long-term stroke patients. Screening tools for unmet social needs such as the Nikolaus-score do not holistically report patients’ needs. Trial registration Clinicaltrials.Gov NCT02320994. Registered 19 December 2014 (retrospectively registered).